EKSISTENSI KEARIFAN LOKAL BACAROTAI DI KANAGARIAN SUNGAI TANANG KECAMATAN BANUHAMPU KABUPATEN AGAM - feronisa edriani; nofrion nofrion (DEPARTEMEN GEOGRAFI FIS UNP, 2019)
The article was written to describe the history, procession, noble values, obstacles and preservation efforts of Local Wisdom “Bacarotai” in Kanagarian Sungai Tanang, Banuhampu District, Agam Regency. The type of research is qualitative descriptive. The informants ar Sungai Tanang village headman, traditional leaders, Bundo Kanduang, community leaders and mosque administrators. Data was collected by in-depth interviews and documentation studies. This research found that (1) the local wisdom of Bacarotai originating from the discussion of Mamak Kaum who wanted Nagari Sungai Tanang to have a large pond (Tabek Gadang) and cultivated it into prohibited fish except when Maoyong or work together to fishing and sell the fish. The remaining fish after Maoyong is given for Bacarotai (2) The Bacarotai procession begins with holding a paid fishing pole which is then calmed for six months, the day before Bacarotai, water is reduced. The next day the people gather at 6 am at the edge of Tabek Gadang, and then Beduk or Siren is sounded. Simultaneously, the people net the fish with Tangguak. After all the fish are taken, the pond is cleaned from the mud and Tabek Gadang is being repaired at a time, then the procession is closed by spreading the fish seeds again. (3) The noble values of Local Wisdom Bacarotai are hospitality, kinship, togetherness, ‘bagurau’(jest), affection and tolerant (4) Obstacles during Bacarotai are rice fields around Tabek Gadang that need irrigation are disrupted and jammed (5) Bacarotai’s preservation is carried out by creating flashbacks in the form of videos, books and making it one of Indonesia's cultural heritages.